Using transit advertising to improve public engagement with social issues. Issue 5 (16th August 2021) - Wilson, Rick T.; Lohmeier, Jill Hendrickson; Lustick, David S.; Chen, Robert F.
Abstract: Out-of-home advertising has the potential to facilitate informal consumer learning about important societal issues. To test this idea, the authors developed an in-market, 14-month transit advertising campaign to educate commuters about climate change and influence attitudes and beliefs on the issue. A unique brand identity, fully functioning website, Facebook page, and Twitter account were created to increase the legitimacy of the campaign. Study results find that the campaign was successful in changing climate change beliefs, increasing optimism about climate change mitigation, and driving commuters to the website where additional information about climate change could be found. Beyond increasing our understanding of social advertising, the study also broadens our understanding of how out-of-home advertising works to increase brand and ad recognition and influence behavior over time and in a naturalistic environment. Ad design and execution strategies are offered to improve the persuasive impact of both out-of-home advertising and informal education through social advertising campaigns.